Acetamiprid inhibits testosterone synthesis by affecting the mitochondrial function and cytoplasmic adenosine triphosphate production in rat Leydig cells†. Issue 1 (23rd December 2016) - Kong, Deying; Zhang, Jidong; Hou, Xiaohui; Zhang, Shibin; Tan, Jun; Chen, Yuanshou; Yang, Weirong; Zeng, Junwei; Han, Yong; Liu, Xiaohong; Xu, Delin; Cai, Renlian
Abstract: The insecticide acetamiprid is used to control noxious agricultural pests. However, it can cause mammalian toxicity. We evaluated the reproductive toxicity of acetamiprid in adult male Sprague Dawley rats. Rats were given oral acetamiprid alone or with vitamin E for 35 days. Rat plasma testosterone concentration and sperm quality decreased significantly as the levels of luteinizing hormone (LH) increased after exposure. At the same time, acetamiprid increased malondialdehyde and nitric oxide (NO) levels of Leydig cells. Further analysis showed that acetamiprid reduced the adenosine triphosphate (ATP) and cyclic adenosine monophosphate (cAMP) production of Leydig cells, but the expression of luteinizing hormone/choriogonadotropin receptor (LHCGR) and the activity of adenylyl cyclase were not changed. Acetamiprid exposure also significantly diminished protein levels of steroidogenic acute regulatory protein (STAR), hydroxy-delta-5-steroid dehydrogenase, 3 beta- and steroid delta-isomerase cluster (HSD3B), and cytochrome P450, family 11, subfamily a, polypeptide 1 (CYP11A1), and testicular mRNA levels, which are cAMP-dependent proteins that are essential for steroidogenesis. Electron microscopy indicated mitochondrial membrane damage in the Leydig cells of the testes of exposed rats. Vitamin E ameliorated the impairment of acetamiprid on Leydig cells. Our results indicate that acetamiprid causes oxidative stress and mitochondrial damage in Leydig cells and inhibits the synthesis of testicular ATP and cAMP. Acetamiprid disrupts subsequent testosterone biosynthesis by decreasing the rate of conversion of cholesterol to testosterone and by preventing cholesterol from entering the mitochondria within the Leydig cells. These effects caused reproductive damage to the rats. Summary Sentence: Mitochondrial inner membrane damage may be the mechanism by which acetamiprid inhibits the testosterone secretion of testicular interstitial Leydig cells.